2013
DOI: 10.18632/oncotarget.1546
|View full text |Cite
|
Sign up to set email alerts
|

AID-induced remodeling of immunoglobulin genes and B cell fate

Abstract: Survival and phenotype of normal and malignant B lymphocytes are critically dependent on constitutive signals by the B cell receptor (BCR) for antigen. In addition, either antigen ligation of the BCR or various mitogenic stimuli result in B cell activation and induction of activation-induced deaminase (AID). AID activity can in turn mediate somatic hypermutation (SHM) of immunoglobulin (Ig) V regions and also deeply remodel the Ig heavy chain locus through class switch recombination (CSR) or locus suicide reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 105 publications
0
22
0
1
Order By: Relevance
“…Before the occurrence of DSBs, CSR is initiated by AID and the initial outcome of AID targeting can be the occurrence of base substitutions following cytidine deamination 12,14,15,21 . To gain an insight into this initial targeting, we analysed mutations in S regions and observed that both the S m donor and S g1 acceptor regions are less targeted by AID during IgG 1 CSR in 3 0 RR-deficient mice as compared with wt animals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Before the occurrence of DSBs, CSR is initiated by AID and the initial outcome of AID targeting can be the occurrence of base substitutions following cytidine deamination 12,14,15,21 . To gain an insight into this initial targeting, we analysed mutations in S regions and observed that both the S m donor and S g1 acceptor regions are less targeted by AID during IgG 1 CSR in 3 0 RR-deficient mice as compared with wt animals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…20 The unique cytoplasmic tails of IgM and IgG BCR produce qualitatively different signaling outputs in antigen-experienced B cells. 35 In particular, switched memory B cells are prone to generate a large number of plasma cells whereas IgM 1 memory B cells reinitiate a GC reaction upon antigenic challenge. 36,37 The maintenance of IgM BCR could thus contribute to the frozen GC phenotype of FL B cells that is established very early during lymphomagenesis process and is associated with a high risk of additional genetic events.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a new AID-dependent recombination event, joining Sμ and switch-like regions located in the 3′RR at the end of the IgH locus, deletes all IgH constant genes and induces B cell apoptosis 27 , again regulating the B cell compartment. So AID and B cell fate are intrinsically linked (for review 28 ) and precise mechanisms governing AID activity, subsequent B cell outcome, and humoral immune responses are important fields of investigation.…”
Section: Somatic Hypermutation Class Switch Recombination and B Celmentioning
confidence: 99%